Áreas marginais a corpos hídricos urbanos: delimitação e zoneamento ambiental. Área piloto: bacia do córrego Santa Maria Madalena em São Carlos, SP - Felicio, Bruna da Cunha (2012)
This research seeks to meet the demand for information assisting public administrators in making decisions about urban development. Along these lines, this case study on Santa Madalena Stream watershed (SMSW), São Carlos, Brazil, aims to supplement Federal Law No. 12,651, of May 25, 2012, which establishes permanent protection areas (PPAs) adjacent to water bodies. To this end, it considers local specificities and provides a tool for protecting watersheds and improving the quality of life of surrounding populations. The main objective of this study is to develop and propose criteria and guidelines for the protection of urban watersheds through an environmental zoning (ZA) process conducive to establishing land occupancy modes and priorities as well as drawing up legal regulations on a local scope. This study indicates that the aforementioned law should take into account local demands and specificities while abiding by its fundamental principles. The procedure presented herein may ultimately contribute to public administrators‟ strategic planning for land use and occupancy and supplementing Federal Law no. 12,651 in order to promote environmental protection and urban development consistent with preserving PPAs. In carrying out this study, the researchers aimed to contribute to public administrations‟ urban planning and environmental management. In this manner, it provides a basis for establishing priority areas for environmental protection and improving public policies on this subject